Surfactant protein D, Club cell protein 16, Pulmonary and activation-regulated chemokine, C-reactive protein, and Fibrinogen biomarker variation in chronic obstructive lung disease - Lock-Johansson, Sofie (Respir Res, 2014)
Chronic obstructive pulmonary disease (COPD) is a multifaceted condition that cannot be fully described by the severity of airway obstruction. The limitations of spirometry and clinical history have prompted researchers to investigate a multitude of surrogate biomarkers of disease for the assessment of patients, prediction of risk, and guidance of treatment. The aim of this review is to provide a comprehensive summary of observations for a selection of recently investigated pulmonary inflammatory biomarkers (Surfactant protein D (SP-D), Club cell protein 16 (CC-16), and Pulmonary and activation-regulated chemokine (PARC/CCL-18)) and systemic inflammatory biomarkers (C-reactive protein (CRP) and fibrinogen) with COPD. The relevance of these biomarkers for COPD is discussed in terms of their biological plausibility, their independent association to disease and hard clinical outcomes, their modification by interventions, and whether changes in clinical outcomes are reflected by changes in the biomarker.